KNOWLEDGE OF ENTREPREUSHIP IN CASH WAQF IN INTERNATIONAL COUNCIL FOR SMALL BUSINESS BRANCH SURABAYA - Saputra, Hendra Eka; Abshari, Han Hanif (Program Studi Ekonomi Islam FEI UNIDA Bogor, 2019)
This research is based on Law No. 41 of 2004 concerning endowments. The establishment of the Indonesian Waqf Board (BWI) triggered the existence of cash waqf. The problem that arises is the role of entrepreneurs in money waqf programs. The research method uses a qualitative case study approach of the International Council for Small Business (ICSB Surabaya city branch). The results of this study that entrepreneurship in this case ICSB Surabaya branch of the city is still unfamiliar with cash waqf and argues that cash waqf can help the Indonesian economy, and assess BWI performance is still not optimal.